2003
DOI: 10.1093/nar/gkg315
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate TBP-like protein (TLP/TRF2/TLF) stimulates TATA-less terminal deoxynucleotidyl transferase promoters in a transient reporter assay, and TFIIA-binding capacity of TLP is required for this function

Abstract: The TBP-like protein (TLP/TRF2/TLF), which belongs to the TBP family of proteins, is present in all metazoan organisms. Although the human TLP has been reported to interfere with transcription from TATA-containing promoters, the transcription activation potential of TLP in higher animals is obscure. We previously demonstrated that artificially promoter-recruited TLP behaves like an unconventional transcriptional activator. In this study, we investigated the effects of TLP on TATA-less promoters of mouse and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The upstream and downstream promoters are TATA-less and TATA-containing promoters, respectively. The p21 promoter(s) in p21luc1 was not activated by TLP but rather inhibited as observed previously for several TATA-containing promoters (28,34). Because p21luc1 harbors two tan- dem-orienting promoters, the effect of TLP on the downstream promoter alone was not elucidated from this construct.…”
Section: Tlp Negatively Affects G 1 -S Transition In Cell Cyclementioning
confidence: 62%
See 3 more Smart Citations
“…The upstream and downstream promoters are TATA-less and TATA-containing promoters, respectively. The p21 promoter(s) in p21luc1 was not activated by TLP but rather inhibited as observed previously for several TATA-containing promoters (28,34). Because p21luc1 harbors two tan- dem-orienting promoters, the effect of TLP on the downstream promoter alone was not elucidated from this construct.…”
Section: Tlp Negatively Affects G 1 -S Transition In Cell Cyclementioning
confidence: 62%
“…By using TLP knock-out chicken DT40 cells, we demonstrated that TLP inhibits G 2 -M transition (32). Although TLP has no obvious sequence-specific DNA binding activity, many lines of evidence indicate that TLP has a transcription-activating ability (33,34). Through cell-based transient promoter assays, we have demonstrated that TLP activates several promoters that lack a TATA box, whereas TATA-containing promoters are repressed for an unknown reason (28,34,35).…”
Section: Waf1/cip1mentioning
confidence: 88%
See 2 more Smart Citations
“…We postulate that a testis-specific transcription preinitiation complex containing both TAF7L and TRF2 is formed and targeted to a subset of "TATA-less" promoters to regulate postmeiotic Trf2-dependent gene expression (43)(44)(45) (Fig. S9).…”
Section: Discussionmentioning
confidence: 99%